Scientific whaling and how philosophy of science can help break the international deadlock - David Coady; Brendan Gogarty; Jeffrey McGee (2017)
Despite widespread public interest on the topic of whaling, there is at present relatively little work on how philosophy might contribute to analysis of the status of whaling in international law. When philosophers have looked at the topic of whaling, they have confined their attention to a fairly narrow set of ethical questions, such as whether international law should permit certain forms of traditional indigenous whaling or extend legal rights to whales themselves. However, there is another important issue which has so far been largely neglected by philosophy, even though it is at the forefront of current international legal disputes over the status of whaling: the issue of so-called ‘scientific whaling’. This article considers the international legal dispute between Australia, New Zealand and Japan over the latter’s lethal harvesting of whales in the Southern Ocean, and the recent attempt at resolution by the International Court of Justice. On its face, this required that the Court demarcate ‘scientific’ from ‘unscientific’ activity; however, it effectively baulked at this task. The authors argue that this approach of the Court was unfortunate, and that demarcating science from commerce is not only achievable in philosophy, but might also inform international legal practice. Resolving this issue is important for genuine progress to be made in the current international stand-off over Japanese whaling in the Southern Ocean.